REVITALIZATION OF MOSQUE MANAGEMENT MODELS AND THEIR APPLICATION IN SOCIAL CAPITAL - Muhlis, Muhlis; Sagara, Yusar; Amani, Zulfa (Al-Qalam, 2023)
The revitalization of mosque management at Kurir Langit Mosque aims to restore its function as a place of worship and a relevant social practice aligned with the current needs of the Muslim community by reinstating the practices of the early era of Islam during the time of Prophet Muhammad (peace be upon him) and his companions. The research objective is to examine the strategies for revitalizing mosque management models and their implementation in the context of social capital at Kurir Langit Mosque. This study utilizes a qualitative method with a field research approach. The research findings reveal that the revitalization of Kurir Langit Mosque's management has brought about significant transformation inmosque management, fundraising, and various social practices, thereby introducing the concept of social capital within the community. The modern concept of revitalization at Kurir Langit Mosque involves a return to the roots of early Islam, adopting early Islamic practices, and making the mosque a centre for education and empowerment. Community funds are managed meticulously, combining religious values with educational services, primarily funded through endowments, zakat, almsgiving, and donations, enabling the mosque to operate independently. A comprehensive social welfare program focusing on education,well-being, and empowerment is implemented with a mentorship-based approach, fostering positive change and reducing reliance on aid and donations.